Career trajectories into undereducation. Which skills and resources substitute formal education in the intergenerational transmission of advantage?*. (August 2020) - Wiedner, Jonas; Schaeffer, Merlin
Highlights: Cognitive ability and openness predict undereducation; conscientiousness does not. Social origin is a main determinant of undereducation. Undereducation is an important component of social reproduction. Similar results for the United Kingdom and for Germany. Abstract: A significant share of employees in Europe has less formal training than is required by their job; they are undereducated. We use harmonized panel data from the United Kingdom and Germany to investigate the skills and resources allowing the undereducated to develop careers in occupations supposedly beyond their reach. Our theoretical approach complements individual-centered labor market theory with an intergenerational mobility perspective which regards undereducation as a form of family status maintenance. Our empirical results show that persons whose (non-)cognitive skills exceed their formal education are more likely to be undereducated in the cross-section, and to enter undereducated employment or be promoted into it throughout the life course. Yet beyond individual merit, parental socio-economic status is a similarly-important predictor of these outcomes; our analyses even trace a significant share of the importance of (non-)cognitive skills to it. To complete our intergenerational argument, we finally demonstrate that undereducation acts as a pathway to the intergenerational reproduction of earnings inequality – more so, in fact, than the avoidance of overeducation. These results are remarkably similar across the UK and Germany, although some country differences suggest higher skill-induced career mobility in Britain and stronger origin effects in Germany. We discuss promising avenues for further comparative research in the conclusion.